"What a match!": The specific role of resources in the relation between demands and vigour in elite sport - Balk, Y. A.; De Jonge, J.; Oerlemans, W. G. M.; Geurts, S. A. E. (Applied Psychology, 2020)
The triple-match principle, as outlined by the Demand-Induced Strain Compensation (DISC) Model, states that resources are most effective when they match particular demands. The present study investigates the role of match in elite sport with regard to the relation between sport-related demands, sport-related resources, and vigour (i.e., physical strength, cognitive liveliness, and emotional energy). We hypothesised that moderating effects of resources on the relation between demands and vigour are most likely when there is a triple-match between demands, resources and vigour, followed by double-match and non-match. A cross-sectional survey study was conducted among 118 semi-professional and professional athletes (70 females, 48 males, M age = 24.7, SD = 6.5). Physical resources moderated (i.e., strengthened) the positive relation between physical demands and physical strength, whereas emotional resources moderated (i.e., buffered) the negative relation between emotional demands and emotional energy. Moderating effects of sportrelated resources on the relation between sport-related demands and vigour occurred more often when there was a triple-match compared to when there was less match or no match at all. These findings indicate that, also in the domain of elite sport, resources do not randomly moderate the relation between demands and well-being. Implications and limitations of the study are discussed.